Pharmacogenetic study of seven polymorphisms in three nicotinic acetylcholine receptor subunits in smoking-cessation therapies. Issue 1 (December 2017) - Pintarelli, Giulia; Galvan, Antonella; Pozzi, Paolo; Noci, Sara; Pasetti, Giovanna; Sala, Francesca; Pastorino, Ugo; Boffi, Roberto; Colombo, Francesca
Abstract Smoking-cessation therapy reduces the risk of smoking-related diseases, but is successful only in a fraction of smokers. There is growing evidence that genetic variations in nicotinic acetylcholine receptor (nAChR) subunits influence the risk of nicotine dependence and the ability to quit smoking. To investigate the role of polymorphisms in nAChR genes on smoking quantity and the outcome of smoking-cessation therapies, we carried out an association study on 337 smokers who underwent pharmacotherapy with varenicline, bupropion, nicotine replacement therapy (NRT) alone, or NRT plus bupropion. Smoking habit and abstention were assessed from the number of cigarettes smoked per day (CPD) and the exhaled CO (eCO), at baseline and up to 12 months. We genotyped seven polymorphisms in genes encoding the nAChR subunitsCHRNA4, CHRNA5, andCHRNB2 . At baseline, both CPD and eCO were associated with polymorphisms in theCHRNA5 locus (rs503464, rs55853698, rs55781567 and rs16969968;P  < 0.01). rs503464, a variant in the 5′-UTR ofCHRNA5, was also associated with short-, mid- and long-term responses to therapy (P  = 0.011, P  = 0.0043, P  = 0.020, respectively), although after correction for multiple testing only the association at the mid-term assessment remained significant (FDR = 0.03). These data support the role of individual genetic makeup in the ability to quit smoking.